2020
DOI: 10.1111/1475-6773.13586
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting preventable hospital readmissions with causal machine learning

Abstract: Objective: To assess both the feasibility and potential impact of predicting preventable hospital readmissions using causal machine learning applied to data from the implementation of a readmissions prevention intervention (the Transitions Program). Data Sources: Electronic health records maintained by Kaiser Permanente Northern California (KPNC). Study Design: Retrospective causal forest analysis of postdischarge outcomes among KPNC inpatients. Using data from both before and after implementation, we apply ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…These characteristics make them particularly appealing for developing risk prediction algorithms that can be deployed at the level of populations for health system planning. While there is an increasing number of risk prediction models intended for clinical use in individuals in an ambulatory setting,25–28 there are few examples of a single, unified model that can be deployed on routinely collected data to regularly support population health and health system management 29. Databases with analogous AHD are available in most single-payer healthcare systems such as the UK, Australia and New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make them particularly appealing for developing risk prediction algorithms that can be deployed at the level of populations for health system planning. While there is an increasing number of risk prediction models intended for clinical use in individuals in an ambulatory setting,25–28 there are few examples of a single, unified model that can be deployed on routinely collected data to regularly support population health and health system management 29. Databases with analogous AHD are available in most single-payer healthcare systems such as the UK, Australia and New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…60 Our analysis, in its current form, although finding limited evidence for heterogeneity in the associations between implementation and readmission and mortality outcomes across levels of predicted risk, might not be able to capture the full extent of whatever treatment effect heterogeneity might exist. 61 Indeed, in our analysis we found that the regression discontinuity estimates of the extent of association between implementation and outcomes for patients at relatively lower risk (25%) tended to be larger than those from the difference-in-differences estimates, which represent an overall association that includes all patients at increased risk (25% to 100%), including high risk patients. This discrepancy was particularly pronounced for post-discharge mortality, where the regression discontinuity estimate suggesting benefit at a relatively lower risk level was statistically significant, but not the overall difference-in-differences estimate.…”
Section: Unanswered Questions and Future Researchmentioning
confidence: 53%
“… 60 Our analysis, in its current form, although finding limited evidence for heterogeneity in the associations between implementation and readmission and mortality outcomes across levels of predicted risk, might not be able to capture the full extent of whatever treatment effect heterogeneity might exist. 61 …”
Section: Discussionmentioning
confidence: 99%
“…Causal inference in machine learning is a relatively new addition to the methodologic arsenal [ 5 ]. The causal forest, a special version of the generalized random forest [ 7 ], is the most widely used method for computing conditional average treatment effects in the medical literature; being used for readmission risk [ 11 ], targeted intervention development [ 6 ], diabetes epidemiology [ 12 ], and identification of risk factors for thyroid disease [ 13 ]. As discussed previously, causal machine learning methods are distinct from traditional supervised machine learning since these models estimate the treatment effect as opposed to risk or prediction.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed previously, causal machine learning methods are distinct from traditional supervised machine learning since these models estimate the treatment effect as opposed to risk or prediction. Further, they are not bound by parametric assumptions common in traditional methods such as regression modeling and are less apt to overfit through application of regularization in the computation [ 8 , 11 ]. These factors, along with the ability to assess conditional average treatment effects in small sample sizes allowed us to perform a more robust analysis of these randomized data.…”
Section: Discussionmentioning
confidence: 99%